Lack of Difference between the Reduced Dose and Full-Dose of Antiretroviral Therapy in Terms of the Decrease in Immune Activation - Nicolè S; Cucchetto G; Lanzafame M; Rigo F; Lattuada E; Concia E; Vento S (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2017)
Virological and immunological effectiveness of reduced doses of antiretrovirals has been shown in two randomized trials and smaller studies. We have now evaluated immune activation in patients on reduced doses of antiretroviral therapy (ART) using HLA-DR+CD8+ lymphocytes as a marker of activation. In an observational, retrospective study we assessed 113 HIV-infected patients who switched from standard combined ART (cART) to reduced dose combinations (cohort 1), while maintaining virological suppression (<20 copies/mL). After a mean time of 36 months on reduced dose therapy, the mean increase in CD4+ lymphocyte numbers was 100 cell/µL (p<0.01) and the mean reduction of HLA-DR+ lymphocytes was 103 cells/µL (p<0.01). We also compared cohort 1 with a cohort of 113 virologically suppressed patients on standard cART (cohort 2). We found no significant differences in the number of CD4+ lymphocytes or in immune activation (mean values of HLA-DR+ absolute number and percentage of total CD8+ lymphocytes). The results of this retrospective study did not identify any immunological differences between reduced antiretroviral dose regimens and standard cART and suggest that reduced dose regimens can progressively reduce immune activation similarly to standard cART.